2003
DOI: 10.1242/jcs.00682
|View full text |Cite
|
Sign up to set email alerts
|

Barrier-to-autointegration factor plays crucial roles in cell cycle progression and nuclear organization inDrosophila

Abstract: Barrier-to-autointegration factor (BAF) is potentially a DNA-bridging protein, which directly associates with inner nuclear membrane proteins carrying LEM domains. These features point to a key role in regulation of nuclear function and organization, dependent on interactions between the nuclear envelope and chromatin. To understand the functions of BAF in vivo, Drosophila baf null mutants generated by P-element-mediated imprecise excision were analyzed. Homozygous null mutants showed a typical mitotic mutant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
153
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(166 citation statements)
references
References 43 publications
11
153
2
Order By: Relevance
“…The genetic null phenotype for BAF was previously reported in Drosophila melanogaster, based on deletions that removed the entire D-BAF coding sequence (30). Genetic null phenotypes, even for essential genes, are not revealed in Drosophila until the larval-pupal transition, when maternally contributed mRNAs and proteins are finally depleted.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The genetic null phenotype for BAF was previously reported in Drosophila melanogaster, based on deletions that removed the entire D-BAF coding sequence (30). Genetic null phenotypes, even for essential genes, are not revealed in Drosophila until the larval-pupal transition, when maternally contributed mRNAs and proteins are finally depleted.…”
Section: Discussionmentioning
confidence: 93%
“…Loss of D-BAF caused defects in chromatin organization and the appearance of heterochromatin-like clumps of chromatin, similar to our findings in early C. elegans embryos down-regulated for Ce-BAF. Other structural phenotypes in BAF-null Drosophila included abnormal distribution of lamin B and abnormal nuclear shapes in interphase cells (30). In contrast, neither anaphase-bridged chroma- tin nor gapped nuclear envelopes were reported, probably because BAF-deficient Drosophila cells failed to enter mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies have shown that dBAF is essential for viability, with null mutants displaying a typical mitotic phenotype (Furukawa et al 2003). That the loss of neither dMAN1 nor Otefin ( Jiang et al 2008) is lethal suggests one of two possibilities.…”
Section: /Dman1mentioning
confidence: 99%
“…This domain interacts with the small, conserved protein called barrier-to-autointegration factor (BAF) that binds double-stranded DNA and histones (Zheng et al 2000;Cai et al 2001;Laguri et al 2001;Furukawa et al 2003;Liu et al 2003;Montes De Oca et al 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation